Hellboy and the b.p.r.d. 1957 ebook - Mignola, Mike (Hellboy and the B.P.R.D. (2014)., 2023)
Hellboy crisscrosses the globe on missions to track down demonic books, solve the sightings of mysterious creatures, and deal with restless spirits in this gripping collection of one-shots. These stories will let readers get to know some of the human members of the B.P.R.D. and the unique talents they bring to the organization. Even Hellboy needs backup from time to time! All five issues of Hellboy and the B.P.R.D.: 1957 are collected in this paperback with writing by Mike Mignola and Chris Roberson, featuring art by Hellboy Universe veteran Laurence Campbell (B.P.R.D.: The Devil You Know), Stephen Green (Lobster Johnson: Garden of Bones), Shawn Martinbrough (Thief of Thieves), Alison Sampson (Jessica Jones), and Mike Norton (Hellboy and the B.P.R.D.: 1956), plus the short "Happy New Year, Ava Galluci" by Mignola and Ben Stenbeck, featuring colors by Dave Stewart and a bonus sketchbook section. Collects Hellboy and the B.P.R.D.: 1957 one-shots: Family Ties, Forgotten Lives, Falling Sky, Fearful Symmetry, and From Below, and the short "Happy New Year, Ava Galluci" from the Hellboy Winter Special.